Analisis Collaborative Governance Dalam Penerapan Elektronik Kesehatan (E-Kes) Di Kabupaten Bengkulu Tengah - Deni Triyanto; Soehito Efendi; Veny Puspita (PERSPEKTIF, 2021)
The purpose of this research is to analyze collaborative governance in the application of e-kes in Bengkulu Tengah Regency, using descriptive qualitative research methods with indicators of network structure, commitment to a common purpose, trust among the participants, and access to resources ". Data collection techniques through interviews, observation and documentation. The informants of this research are the Secretary of the Bengkulu Provincial Office, the Regency and the authorized officials, policy implementers, the Head of the Puskesmas, and the Puskesmas Operators. The results of the study revealed that the network structure on the collaboration in implementing E-Kes is quite good, such as the development of authority and authority among stakeholders, both from health centers, hospital hospitals, district health offices and Bengkulu Province health offices, commitment to a common purpose, stakeholder commitment is quite good, trust among The participants said that the trust among stakeholders was not good because the infrastructure for implementing e-kes was not supportive, the access to information technology resources involved was not optimal at the health center level. The conclusion is that the collaboration in implementing e-kes in Bengkulu Tengah Regency is not optimal because several indicators still find problems in its application.